New staging system for cutaneous melanoma - Mackiewicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2002)
The American Joint Committe on Cancer (AJCC) formally approved the final version of staging system for cutaneous melanoma. It will become official with publication of the sixth edition of the AJCC Cancer Staging Manual in the year 2002. Major changes compared with the previous version include: (1) evaluation of the melanoma thickness and ulceration (evaluated pathologically) of primary melanoma but not the level of invasion (Clark) with exception for T1 melanomas; (2) the number of metastatic lymph nodes but not their dimensions, and diversion of micro- v. macroscopic metastases; (3) the site of distant metastases and elevated serum lactic dehydrogenase (LDH); (4) upstaging of patients with stage I, II and III melanoma when primary lesion is ulcerated; (5) staging satellite metastases and in-transit into the same group (within stage III); (6) defining clinical and pathological staging. The latter includes information gained from lymphatic mapping and sentiel node biopsy.